Impact of Amaranthus hypochondriacus in nutrition for rabbits on meat quality - Shevchik, R. S.; Shevchik, Rimma; Shevchik, Rimma S.; Shevchyk, R. S.; Shevchik, R.; Шевчик, Римма Святославівна; Duda, Yuliya; Duda, Y. V.; Duda, J. V.; Duda, Julia; Duda, Y.; Duda, J.; et al. (My University, 2021)
Unique properties of Amaranthus hypochondriacus have been extensively utilized in the recent time worldwide both in food technologies and husbandry. An intensive growth of Amaranthus hypochondriacus plants has been made in Ukraine there and, respectively, production of foods based on amaranth is growing, however no research on its use for feeding rabbits is available. Therefore, the study aimed to review the impact of Amaranthus hypochondriacus on slaughter features of rabbits, meat quality including those under storage conditions. The California race rabbits of 60 days age were divided into two groups, 28 animals in each. The rabbits in the study group were fed (by adding to the basal diet) with 20% of amaranth oilcake. The rabbits were slaughtered at age of 120 days. The following key features of meat output and quality performance were determined: pH, moisture content, water-holding capacity, cooking losses, protein and cholesterol content as well as change in pH, microorganisms count, and moisture loss percentage during 9-day storage in chilled state. Amaranthus hypochondriacus effect on the rabbit live weight, hot carcass weight, dressing out percentage, percentage ratio of heart, kidney, liver, lung weight to carcass weight, рН, moisture content, water-holding capacity, and meat morphological structure was determined. Reduction in cholesterol level by 15.07% (р < 0.05) in the meat of rabbits that were fed with Amaranthus hypochondriacus was detected. pH and drip loss percentage were not significantly different among the groups in the shelf-life period. However, it was found out that growth of microorganisms in the meat of rabbits that were fed with Amaranthus hypochondriacus was slowed down: microorganisms count was 1.65 and 1.71 (р < 0.05) times lower than in the control group on the 6th and 9th days of storage, accordingly. The low-cholesterol and bacteriostatic effects of amaranth oilcake in the rabbit nutrition may significantly increase dietary properties of rabbit meat. Use of amaranth oilcake for rabbit fattening has great potential and further studies including the mechanism of antibacterial effect of A. hypochondriacus on the rabbit meat are required. Унікальні властивості Amaranthus hypochondriacus останнім часом широко використовуються у всьому світі як у харчових технологіях, так і в тваринництві. Там в Україні відбувся інтенсивний ріст рослин Amaranthus hypochondriacus, і відповідно зростає виробництво продуктів на основі амаранту, однак досліджень щодо його використання для годівлі кроликів немає. Тому дослідження мало на меті переглянути вплив Amaranthus hypochondriacusщодо особливостей забою кроликів, якості м’яса, включаючи ті, що перебувають в умовах зберігання. Кроликів каліфорнійської породи віком 60 днів було розділено на дві групи, по 28 тварин у кожній. Кроликів у досліджуваній групі годували (додаючи до основного раціону) 20% амарантової макухи. Кроликів забивали у віці 120 днів. Визначено такі ключові особливості вироблення м’яса та показники якості: рН, вміст вологи, вміст води, втрати при варінні, вміст білка та холестерину, а також зміна рН, кількість мікроорганізмів та відсоток втрати вологи під час 9-денного зберігання у охолодженому стані. Amaranthus hypochondriacusВизначено вплив на живу масу кролика, масу гарячої туші, відсоток переробки, процентне співвідношення серця, нирок, печінки, масу легенів до маси туші, рН, вміст вологи, вміст води та морфологічну структуру м’яса. Виявлено зниження рівня холестерину на 15,07% (р <0,05) у м'ясі кроликів, яких годували Amaranthus hypochondriacus. РН та відсоток втрати крапель не суттєво відрізнялися серед груп у період зберігання. Однак було встановлено, що в мікросі кроликів, яких годували Amaranthus hypochondriacus , ріст мікроорганізмів було уповільнено: кількість мікроорганізмів була в 1,65 та 1,71 (р <0,05) разів нижчою, ніж у контрольній групі, на 6 та 9 день зберігання відповідно. Низький вміст холестерину та бактеріостатичний ефект макухи амаранту у харчуванні кроликів може суттєво підвищити дієтичні властивості м’яса кролика. Використання амарантової макухи для відгодівлі кроликів має великий потенціал, і необхідні подальші дослідження, включаючи механізм антибактеріального впливу A. hypochondriacus на м'ясо кролика.
Вплив Amaranthus hypochondriacus у харчуванні кроликів на якість м’яса
Шевчик Римма Святославівна https://orcid.org/0000-0001-7416-8656 Дуда Юлія Вікторівна https://orcid.org/0000-0003-0892-0402 Гавриліна Олена Геннадіївна http://orcid.org/0000-0001-9624-9510 Кунєва Лариса Володимирівна https://orcid.org/0000-0002-4156-2136
Keywords: microorganisms; мікроорганізми; amaranth; амарант; rabbits; кролики; meat quality; якість м’яса; cholesterol; холестерин